Analyzing the Nutritional Awareness, Dietary Practices, Attitudes, and Performance of U-17 Football Players in Ethiopia - Abdi Gudeta Taye; Dessalegn Wase Mola; Md. Hamidur Rahman (OVS LLC, 2024)
Background. Adequate nutrition knowledge is crucial for developing proper eating habits, especially among athletes, as it has a significant impact on sports performance. This underscores the consensus in sports nutrition education among professionals working with athletes. Study purpose. The study aimed to assess the nutritional knowledge, attitudes, and dietary practices of under-17 football club players in Ethiopia. Materials and methods. A descriptive survey research method was used, and standardized questionnaires were randomly distributed to 26 footballers to assess participants' knowledge, attitudes, and dietary practices regarding nutrition. Data were analyzed using the t-test, Pearson coefficient, and one-way ANOVA (p <0.05). Reliability analysis showed a Cronbach's alpha value of 0.83 for the scales measuring attitudes towards eating habits and nutrition knowledge (0.79 and 0.78, respectively). Results. No statistically significant differences (p >0.5) were observed in the data related to eating habits, age, or nutritional understanding. Significant variations in educational backgrounds were noted (p <0.05). Although gender and source were not recognized as correlates of nutritional knowledge, but age and education were. Conclusions. In summary, the study revealed no significant differences (p > 0.05) in nutrition knowledge scores for age, education, and source of information. However, a significant difference (p<0.05) was found between male and female athletes. Gender correlated with dietary habits, while age, education, and source of information did not. The key factor is to encourage ongoing future vision within sports organizations, nutritionists, and educational institutions to continuously refine and enhance nutrition knowledge, attitudes, and practice programs for U-17 players. It is also important to ensure sustainable relevance and effectiveness in the evolving landscape of sports and nutrition.